State Regulation of the Development of the Agro-Industrial Complex of the Republic of Kazakhstan - KHADYS, Batyrbyek; SIKHIMBAYEVA, Dinarа; BOZHKARAULY, Altai (Journal of Advanced Research in Law and Economics, 2018)
In the article, we had considered the problems of state regulation of the agro-industrial complex of the Republic of Kazakhstan which include improving the provision of food for the population, maintaining economic parity between agriculture and other branches of the economy, convergence of income levels to agricultural and industrial workers, protecting domestic producers in agro-industrial production, the regulation of the development of the agro-industrial complex is aimed at ensuring food security, the stability of the agro-industrial complex market, the formation of an effective business system, the support of competitive domestic products, and improving the living standards of the rural population through creating conditions for plant management and animal management, processing agricultural raw materials, providing veterinarians and phyto -sanitary safety and technically equip, as well as the development of social and engineering infrastructure. Also the principles and methods of state regulation of the agro-industrial complex are given. The economic and management organizations had proposed measures necessary for state regulation of the agro-industrial complex within the country. The factors that should be taken into account when developing and implementing agrarian policy are indicated.